Renewable Energy in Turkey : A Study of the Development and Growth of Solar Energy - Caba, Furkan (2025)
Renewable Energy in Turkey: A Study of the Development and Growth of Solar Energy This thesis analyzes the growth and development of solar energy in Turkey from historical and policy perspectives. It reviews global energy trends, highlighting renewables’ rise and ongoing fossil-fuel dependence. Using data from the International Energy Agency, REN21, and national sources, it traces Turkey’s energy demand and import reliance. It assesses solar potential via radiation maps and sunshine-duration data, showing high values for both photovoltaic and thermal applications. It investigates Turkey’s policy framework, including the Renewable Energy Support Mechanism (YEKDEM), Renewable Energy Law No. 5346, and the YEKA tender model. It evaluates effects on licensed and unlicensed solar installations, domestic-manufacturing incentives, and permit simplification. Installed capacity rose from under 0.5 GW in 2014 to over 12 GW by 2023, driven by feed-in tariffs, tax exemptions, and land allocation. Solar investments concentrate in the Mediterranean, Southeastern Anatolia, and Central Anatolia. The study addresses grid-integration challenges, storage gaps, and regional imbalances. A comparison with China, the USA, Germany, and India examines capacity, policy mechanisms, storage integration, and domestic-panel production, identifying gaps and lessons for Turkey. Technological advances have decreased solar electricity costs, but battery storage and grid flexibility remain essential. Institutional barriers—such as bureaucratic delays and legal uncertainties—limit progress. The thesis proposes clear, consistent incentives; stronger support for local manufacturing; expanded storage investment; and better institutional coordination. These findings clarify solar-energy dynamics in an emerging market. The recommendations can help policymakers boost Turkey’s energy security, reduce import dependence, and meet renewable targets.